2015
DOI: 10.1103/physrevlett.115.167201
|View full text |Cite
|
Sign up to set email alerts
|

Emergent SU(3) Symmetry in Random Spin-1 Chains

Abstract: We show that generic SU(2)-invariant random spin-1 chains have phases with an emergent SU(3) symmetry. We map out the full zero-temperature phase diagram and identify two different phases: (i) a conventional random singlet phase (RSP) of strongly bound spin pairs (SU(3) "mesons") and (ii) an unconventional RSP of bound SU(3) "baryons", which are formed, in the great majority, by spin trios located at random positions. The emergent SU(3) symmetry dictates that susceptibilities and correlation functions of both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 36 publications
5
47
0
Order By: Relevance
“…In addition, we report that (not shown) C α av (x) oscillates with period of 3, as a consequence of the antiferromagnetic SU(3)symmetric character of the ground state. 42 As expected, we observed that both correlations are identical within the DMRG error.…”
Section: B the Disordered Bilinear-biquadratic Spin-1 Chainsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, we report that (not shown) C α av (x) oscillates with period of 3, as a consequence of the antiferromagnetic SU(3)symmetric character of the ground state. 42 As expected, we observed that both correlations are identical within the DMRG error.…”
Section: B the Disordered Bilinear-biquadratic Spin-1 Chainsupporting
confidence: 87%
“…We then focus on the case θ = π 4 which exhibits exact SU(3) symmetry [i.e., the Hamiltonian (7) becomes H = ∑ i J i Λ i · Λ i+1 + const] placing the system in the Baryonic RS phase. 42 In Fig. 3, we plot the arithmetic average correlations C α av (x) Eq.…”
Section: B the Disordered Bilinear-biquadratic Spin-1 Chainmentioning
confidence: 99%
“…The random Heisenberg Antiferromagnetic spin chain is the first model where SDRG has been introduced [1]. After the various works already reviewed in [3], more recent studies include the effects of next-nearest-neighbor interaction in d = 1 [58], the case of wealkly coupled chains [59], models in dimension d = 2 [60][61][62], as well as the generalizations to various type continuous symmetry (SU (3), SU (N ), SO(N )) considered in the series of papers [63][64][65][66][67], where different types of random singlet phases are identified via SDRG and the low-energy behaviour is controlled by infinite disorder fixed points.…”
Section: B Models With Continuous Symmetrymentioning
confidence: 99%
“…Randomness has been shown to modify the characteristics of phase transi- * These two authors contributed equally. tions [34,35], as well as transition a spin system from one universality class to another [36,37] and is integral to the emergence of interesting phases such as the Griffiths and random singlet phases (RSPs) [38][39][40]. Recently a lot of attention has been devoted to the mechanism of manybody localisation in 1D and 2D systems [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%